Serotonergic Psychedelics Rapidly Modulate Evoked Glutamate Release in Cultured Cortical Neurons - Petrušková, Aneta; Guhathakurta, Debarpan; Akdaş, Enes Yağız; Perelló-Amorós, Bartomeu; Frischknecht, Renato; Weiss, Eva-Maria; Páleníček, Tomáš; Fejtová, Anna (Journal of neurochemistry, 2025)
The serotonergic psychedelics psilocybin, LSD and DMT hold great promise for the development of new treatments for psychiatric conditions such as major depressive disorder, addiction and end-of-life anxiety. Previous studies in both animals and humans have confirmed the effects of these drugs on neuronal activity and plasticity. However, the understanding of the mechanisms of action of these substances is limited. Here we show rapid effects of psychedelics on presynaptic properties, using live cell imaging at the level of single synapses in primary rat cortical neurons. Using the genetically encoded reporter of synaptic vesicle fusion synaptopHluorin, we detected a reduced fraction of synaptic vesicles that fused in response to mild or strong electrical stimulation 3-30 min after application of serotonergic psychedelics. These effects were transient and no longer present 24 h after treatment. While DMT only reduced the total recycling pool, LSD and psilocin also reduced the size of the readily releasable vesicle pool. Imaging with the sensors for glutamate, iGluSnFR, and presynaptic calcium, synGCaMP6, showed that while psilocin and DMT increased evoked glutamate release, LSD and psilocin reduced evoked presynaptic calcium levels. Interestingly, psilocin also affected short-term plasticity leading to a depression of responses to paired stimuli. The rapid and drug-specific modulation of glutamatergic neurotransmission described in this study may contribute to distinct anxiolytic and antidepressant properties of serotonergic psychedelics.
Keywords: halucinogeny; psilocybin; Psilocybin; LSD; Tryptamines; Glutamic Acid; krysa rodu Rattus; Hallucinogens; zvířata; neurony; Cells, Cultured; mozková kůra; Cerebral Cortex; tryptaminy; potkani Sprague-Dawley; Serotonin Agents; Synaptic Vesicles; kultivované buňky; Neurons; Rats; synaptické vezikuly; Rats, Sprague-Dawley; Animals; Lysergic Acid Diethylamide; serotoninové látky; kyselina glutamová